Physico‐chemical characteristics of roselle (Hibiscus sabdariffa L.) - Wong, Peng‐Kong; Yusof, Salmah; Ghazali, H.M.; Che Man, Yaakob (Emerald, 2002)
The physico‐chemical characteristics of roselle from Malaysia were studied. The parameters analysed included size, weight, pH, titratable acidity, soluble solids, anthocyanin contents, organic acids and sugars. Succinic and oxalic acids were the predominant organic acids found in roselle while glucose was the major sugar present. The present study was also conducted to determine and quantify the most biologically effective natural antioxidants present in roselle. Ascorbic acid, β‐carotene and lycopene, were separated, identified and quantified by HPLC. The amounts of ascorbic acid, β‐carotene and lycopene contents were 141.09mg/100g, 1.88mg/100g and 164.34μg/100g, respectively. The individual anthocyanin in roselle was characterised by TLC and HPLC. Delphinidin‐3‐sambubioside and cyanidin‐3‐sambubioside were the main anthocyanin present in roselle.